2004
DOI: 10.1194/jlr.m300363-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the C1431T and Pro12Ala PPARγ gene variants on plasma lipids and diabetes risk in an Asian population

Abstract: We investigated the association of C1431T and Pro12Ala polymorphisms at the peroxisome proliferatoractivated receptor ␥ (PPAR ␥ ) locus with plasma lipids and insulin resistance-related variables, according to diabetes status, in a large and representative Asian population from Singapore consisting of 2,730 Chinese, 740 Malays, and 568 Indians. Moreover, we estimated the diabetes risk and examined gene-nutrient interactions between these variants and the ratio of polyunsaturated fatty acid to saturated fat (SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 48 publications
9
88
3
Order By: Relevance
“…Genetic differences may also account for their higher susceptibility to insulin resistance and type 2 diabetes mellitus. A few studies in the population have indicated possible differences in the modulating effect of the Pro-Ala polymorphism in the peroxisome proliferator-activated receptor γ compared with white populations [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic differences may also account for their higher susceptibility to insulin resistance and type 2 diabetes mellitus. A few studies in the population have indicated possible differences in the modulating effect of the Pro-Ala polymorphism in the peroxisome proliferator-activated receptor γ compared with white populations [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the Ala12 allele was protective against diabetes in their study; however, this protective effect, attributable to the Ala12 variant, was absent when the Ala12 variant was presentwith the T allele of c161C T 96) . However, no such opposite interaction or additive effects between c.161C T and p.Pro12Ala was confirmed in another study, and the T allele was associated with a decreased risk of diabetes 97) . Reduced coronary artery disease risk and lower TG were associated with the T allele 98,99) , but a cohort study also indicated an association with higher coronary risk 96) .…”
Section: Other Ppar Gene Variantsmentioning
confidence: 93%
“…Therefore, it is reasonable to believe that mortality in the nonagenarian/centenarian Adjusted multiple logistic regression was used to adjust for covariates OR odds ratio, Unadjusted Wald Chi-square test with df=1 was used, Model 1 adjustment made with covariates which might be associated with cognitive function at baseline (P<0.05 shown in Table 1), Model 2 adjustment made with covariates which might be associated with Pro12Ala (P<0.05 shown in Table 2), Model 3 adjustment made with all the covariates group may alter the association between dementia and Pro12Ala Polymorphism in PPAR-γ2. In addition, the prevalence of Ala12 allele varied greatly in different ethnic populations, with the prevalence rate being much lower in Asians than in Caucasians (Chuang et al 2001;Tai et al 2004). Therefore, ethnicity might also be an influencing factor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of Ala12 allele varied greatly among different ethnic populations, with the prevalence being much lower in Asians than in Caucasians (Chuang et al 2001;Tai et al 2004). The relationship between Pro12Ala polymorphism in PPAR-γ2 and dementia in the very-elderly population might be different from that in old people aged 60 years and above, and the allele frequency of Ala12 in PPAR-γ2 varies greatly in different ethnic populations.…”
Section: Introductionmentioning
confidence: 98%